The parentpreneur edge : - Kirk, Julie Lenzer (John Wiley & Sons, 2007)
Successful parenting skills can be put to great use when you journey down the exciting path of entrepreneurship. This book will help readers make that important connection." -Monica Smiley, Publisher and CEO, Enterprising Women magazine